2019
DOI: 10.1037/ser0000264
|View full text |Cite
|
Sign up to set email alerts
|

State-wide university implementation of an online platform for eating disorders screening and intervention.

Abstract: The Internet-based Healthy Body Image (HBI) Program platform uses online screening to identify individuals at low risk for, high risk for, or with an eating disorder (ED) and then directs users to tailored, evidence-based online/mobile interventions or referral to in-person care to address individuals' risk/clinical status. We examined findings from the first state-wide deployment of HBI over the course of 3 years in Missouri public universities, sponsored by the Missouri Eating Disorders Council and the Misso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 33 publications
5
41
0
Order By: Relevance
“…Screen respondents in the current study self‐selected to complete the online screening tool, which likely explains the much greater level of eating disorder pathology in this sample. In our work implementing an online platform for eating disorders screening and intervention across public universities in the state of Missouri in the U.S. (Fitzsimmons‐Craft et al, ) and as part of a randomized controlled trial in 28 geographically diverse U.S. universities (Fitzsimmons‐Craft et al, ), we similarly demonstrated a high level of eating disorder risk in those who chose to participate in the online screen. This is a key finding as it suggests the current screen attracts respondents with elevated eating disorder pathology and thus, when disseminated widely, has the capability of increasing detection and access to care for individuals at risk for or with eating disorders.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Screen respondents in the current study self‐selected to complete the online screening tool, which likely explains the much greater level of eating disorder pathology in this sample. In our work implementing an online platform for eating disorders screening and intervention across public universities in the state of Missouri in the U.S. (Fitzsimmons‐Craft et al, ) and as part of a randomized controlled trial in 28 geographically diverse U.S. universities (Fitzsimmons‐Craft et al, ), we similarly demonstrated a high level of eating disorder risk in those who chose to participate in the online screen. This is a key finding as it suggests the current screen attracts respondents with elevated eating disorder pathology and thus, when disseminated widely, has the capability of increasing detection and access to care for individuals at risk for or with eating disorders.…”
Section: Discussionmentioning
confidence: 67%
“…Responses are used to categorize individuals into one of seven possible DSM‐5 diagnoses or two risk categories: (1) anorexia nervosa (AN); (2) bulimia nervosa (BN); (3) binge eating disorder (BED); (4) subclinical bulimia nervosa (sub‐BN); (5) subclinical binge eating disorder (sub‐BED); (6) unspecified feeding or eating disorder (UFED); (7) avoidant/restrictive food intake disorder (ARFID); (8) high risk for an eating disorder; or (9) not at risk for an eating disorder. The SWED screening algorithm was validated in college‐age women, with sensitivities ranging from 0.68 (sub‐BN) to 0.90 (AN) and specificities ranging from 0.79 (sub‐BED) to 0.99 (AN) compared to diagnostic interview (see Graham et al, for additional information), and has been used in past research among both men and women (Fitzsimmons‐Craft et al, ). The question, “Are you currently in treatment for an eating disorder?” (with response options of: “no”; “yes”; and “not currently, but in the past” provided) was used to assess eating disorder treatment status.…”
Section: Methodsmentioning
confidence: 99%
“…Reach is defined as the number of people who are offered a service relative to the number of people eligible to receive it, and engagement is defined as uptake and/or adherence to a service. For example, in two initiatives we conducted to implement online screening and intervention for eating disorders on university campuses in the U.S., <3% of the student body completed screening (Fitzsimmons‐Craft et al, ; Fitzsimmons‐Craft et al, ). Similar results were observed for an Internet‐based eating disorder intervention delivered in an Irish university setting (Lindenberg, Moessner, Harney, McLaughlin, & Bauer, ).…”
Section: Introductionmentioning
confidence: 99%
“…To improve uptake, a research team would identify the optimization criterion. For instance, Fitzsimmons‐Craft, Firebaugh, et al () found 50% uptake of digital programs among a university sample following an online screen; surpassing this number could be the target. Then, strategies would be tested that address factors impacting uptake, like varying the type of feedback users receive following screening.…”
Section: Improving Intervention Uptakementioning
confidence: 99%
“…Despite the successes in identifying individuals with EDs in need of intervention, gaps remain in optimizing outcomes for these individuals: (a) screens do not reach all of those in need; (b) there is a large treatment gap between the number of individuals in need of and who receive treatment for an ED (Hart, Granillo, Jorm, & Paxton, ); (c) the number of individuals who follow through on treatment recommendations after a screen is suboptimal (DeBar et al, ); and (d) among those who do receive treatment, many individuals fail to complete a full course of treatment or achieve a desired outcome within a set time frame (Bauer & Moessner, ; Eisenberg et al, ; Fitzsimmons‐Craft, Balantekin, Eichen, et al, ; Fitzsimmons‐Craft, Balantekin, Graham, et al, ; Fitzsimmons‐Craft, Eichen, et al, ; Fitzsimmons‐Craft, Firebaugh, et al, ; Kazdin, Fitzsimmons‐Craft, & Wilfley, ; Lindenberg, Moessner, Harney, McLaughlin, & Bauer, ).…”
Section: Introductionmentioning
confidence: 99%